The Impact of Android Module-Based Inquiry Flipped Classroom Learning on Mathematics Problem Solving and Creative Thinking Ability - Ariani, Dessy Noor; Sumantri, Mohamad Syarif; Wibowo, Firmanul Catur (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This research uses the Android module based on a strategy called "inquiry-based learning" and "flipped classroom" to help people utilize their cross-disciplinary skills in complex real-world situations. This experiment showed how the Android module-based inquiry flipped classroom learning affects math pre-service teachers' ability to solve mathematical problems and think creatively in geometry. In the third term, 123 students were randomly assigned Android module-based inquiry flipped classroom learning, PowerPoint module-based conventional flipped learning, or conventional learning. The study found that math pre-service teachers were much better at solving mathematics problems and creative thinking when using Android module-based inquiry flipped classroom learning because its use effectively extends learning time, permits the acquisition of more knowledge, and encourages a collective responsibility for learning in order to engage in the process of deeper learning. This type of learning also helps them learn how to deal with real-world problems that they may face in their future jobs. This implication can guide instructional designers on how to help students solve math problems and think creatively.